Decreased peak expiratory flow in pediatric passive smokers - Fitri Yanti; Muhammad Ali; Ridwan M. Daulay; Wisman Dalimunthe; Rini Savitri Daulay (Paediatrica Indonesiana, 2011)
Background Indonesia ranks fifth among countries with the highest aggregate levels of tobacco consumption in the world. Infants and children exposed to environmental tobacco smoke have increased rates of asthma, respiratory and ear infections, as well as reduced lung function. The effects of tobacco smoke exposure on lung function in children have been reported to be dependent on the source of smoke and the length and dose of exposure. Lung function may also be affected by a child’s gender and asthma status.